The effects of the water crisis on population dynamics in the City of Flint, Michigan. Issue 1 (2nd January 2018) - Morckel, Victoria; Rybarczyk, Greg
ABSTRACT: Since 2014, residents of Flint, Michigan have dealt with the effects of lead in their municipal system in a series of events known as the Flint water crisis. While several studies have examined the health effects of the crisis and changes in water lead levels over time, no study has considered whether the crisis has resulted or could result in residents leaving the city. To explore this question, we surveyed 405 Flint residents and used quantitative and qualitative methods, as well as exploratory spatial data analysis, to test five hypotheses about the water crisis and population dynamics. We found that population loss has not yet accelerated, but nearly half of residents are considering leaving. This consideration was true regardless of residents' demographics or where they lived in the city. We also discovered that perceptions of the water's safety and its health effects, more than actual water lead levels, predicted whether one is considering leaving. Overall, our results suggest that as water infrastructure quality deteriorates, population loss could accelerate, resulting in a recursive relationship whereby the city's population and its infrastructure continue to decline.